FORMULASI CUSTOMER ENGAGEMENT BERBASIS ISLAMIC SERVICE EXCELLENCE, EMOTIONAL ATTACHMENT, DAN EXPERIENTIAL VALUE TERHADAP LOYALITAS NASABAH SYARIAH - Indra; Fitri Fitri; Ela Laela Ela; AMNA AMNA; Dipa Teruna Awaludin Dipa (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study aims to analyze the influence of Islamic Service Excellence, Emotional Attachment, and Experiential Value on Sharia Customer Loyalty in the Islamic banking industry in Indonesia. This study employed a quantitative approach using Structural Equation Modeling Partial Least Square (SEM-PLS). The research sample consisted of 325 active Islamic bank customers selected using purposive sampling techniques. Data collection was conducted through questionnaires based on a five-point Likert scale. Data analysis was performed using SmartPLS 4 through outer model and inner model testing, including validity, reliability, R-Square, Q-Square, effect size, bootstrapping, and hypothesis testing. The results indicate that Islamic Service Excellence has a positive and significant effect on Sharia Customer Loyalty. Emotional Attachment is proven to be the most dominant variable affecting customer loyalty. Furthermore, Experiential Value also positively influences Sharia Customer Loyalty. This study contributes theoretically to the development of customer engagement based on Islamic values and provides practical implications for Islamic banks in improving customer loyalty through Islamic service quality, emotional relationships, and valuable service experiences. Keywords: Islamic Service Excellence, Emotional Attachment, Experiential Value, Loyalitas Nasabah Syariah, Customer Engagement